Integrated analysis of phosphoproteome and ubiquitinated proteome in rice endosperm under high temperature stress - PANG Yuehan; YING Yining; XU Feifei; BAO Jinsong (浙江大学学报. 农业与生命科学版)
The metabolism of rice endosperm depends on the precise regulation of several post-translational modification (PTM)-based signaling networks, including phosphorylation and ubiquitination modifications. This study, integrating analysis of proteins from phosphoproteome and ubiquitinated proteome, identified 143 proteins with both phosphorylated and ubiquitinated sites, providing a basis for understanding the crosstalk mechanism between phosphorylation and ubiquitination modifications in rice endosperm. On the one hand, phosphorylation modification of key proteins involved in the ubiquitin-proteasome system contributed to the regulation of ubiquitination modification; on the other hand, ubiquitination modification of protein kinases and phosphatases might affect the phosphorylated signaling network. Under high temperature stress, phosphorylation and ubiquitination modifications jointly regulated the synthesis pathway of phenolic compounds, ultimately affecting the ability of phenolic compounds to scavenge reactive oxygen species and plant resistance to stress. Several enzymes related to starch metabolism possessed both phosphorylation and ubiquitination modifications, and 18 pairs of sites with different modification types appeared adjacent to the same protein, revealing the crosstalk mechanism between different modifications and the synergistic regulation of starch metabolism by phosphorylation and ubiquitination modifications under high temperature stress.